ANALISIS KEBIJAKAN IMIGRASI DONALD TRUMP BERDASARKAN KONSEP WELFARE STATE - Hayati, Dewi Pathul; Pramana , Gede Indra; Erviantono , Tedi (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
Welfare State theory underlines the state's responsibility to ensure a minimum standard of living for all its citizens, a concept first implemented by Germany under Otto Von Bismarck in the 1850s. In the context of President Donald Trump's immigration policies, there are efforts to create prosperity for Native Americans through increasing job opportunities and access to resources. However, the policy is also responsible for the welfare of immigrants living in the country. Unfortunately, Trump's policies are influenced by prejudice and insecurity about foreign threats, with misperceptions about jihad within Islam fueling misguided public opinion and spreading Islamophobia. Some of Trump's close advisers, such as Michael Flynn and Steve Bannon, have issued statements stigmatizing Islam as a radical ideology, exacerbating social issues and creating unconstitutional responses against minorities. Trump acts as a securitization actor, depicting America as insecure and trying to take the migration problem seriously through new policies and strong support from parliament. The slogan "Make America Great Again" reflects Trump's determination to restore America's greatness through strict migration policies.